Development and characterization of solid dispersion of piroxicam for improvement of dissolution rate using hydrophilic carriers - Mohammad Barzegar-jalali; Saeed Ghanbarzadeh; Khosro Adibkia; Hadi Valizadeh; Ghobad Mohammadi; Mohammadreza Siahi-Shadbad (BioImpacts, 2014)
Introduction: The main objective of this study was preparation and characterization of solid dispersion of piroxicam to enhance its dissolution rate. Methods: Solid dispersion formulations with different carriers including crospovidone, microcrystalline cellulose and Elaeagnus angustifolia fruit powder and with different drug: carrier ratios were prepared employing cogrinding method. Dissolution study of the piroxicam powders, physical mixtures and solid dispersions was performed in simulated gastric fluid and simulated intestinal fluid using USP Apparatus type II. The physical characterization of formulations were analyzed using powder X ray diffraction (PXRD), particle size analyzer and differential scanning calorimetry (DSC). Interactions between the drug and carriers were evaluated by Fourier transform infrared (FT-IR) spectroscopic method. Results: It was revealed that all of three carriers increase the dissolution rate of piroxicam from physical mixtures and especially in solid dispersions compared to piroxicam pure and treated powders. PXRD and DSC results were confirmed the reduction of crystalline form of piroxicam. FT-IR analysis did not show any physicochemical interaction between drug and carriers in the solid dispersion formulations. Conclusion: Dissolution rate was dependent on the type and ratio of drug: carrier as well as pH of dissolution medium. Dissolution data of formulations were fitted well in to the linear Weibull as well as non-linear logistic and a suggested models.